Semitransparent Printable Mesoscopic Perovskite Solar Cells for Tandem Solar Cells. Issue 11 (1st September 2022) - Ye, Ting; Christoph, Jan; Liu, Jiale; Yang, Ying; Zhang, Wenhao; Tan, Hairen; Mei, Anyi; Rong, Yaoguang; Hu, Yue; Han, Hongwei
Abstract : The boosting efficiency of perovskite solar cells (PSCs) has evoked the interest in applying them in tandem structures, especially perovskite/silicon tandem solar cells. However, the tandem solar cells still face concerns about stability, upscaling, and cost‐effectiveness on the path to commercialization. Herein, an innovative tandem architecture based on the printable mesoscopic perovskite solar cells is proposed. By investigating the effects of indium tin oxide (ITO) particle size, annealing temperature, and dispersant on the performance of ITO mesoporous films, screen‐printable mesoscopic ITO electrode with an electron mobility of 7.5 cm 2 V −1 s −1 and an average visible transmittance of over 80% is successfully obtained. The screen‐printed mesoporous titania, zirconia, and ITO are used as a scaffold and a semitransparent PSC with a champion power conversion efficiency of 9.38% is fabricated infiltrated with perovskites. Further, a perovskite/silicon tandem device which can remain stable for >720 h is demonstrated, highlighting the potential of screen‐printed inorganic scaffold structure in tandem photovoltaic technique. Abstract : A mesoporous indium tin oxide (ITO) transparent electrode is developed, and it is used as the back contact of printable mesoscopic perovskite solar cells (PSCs). This is the screen‐printing process of the mesoscopic printable PSCs.